Batch variability and anti-inflammatory effects of iPSC-derived mesenchymal stromal cell extracellular vesicles in osteoarthritis in vitro model - Palamà, Maria Elisabetta Federica; Gorgun, Cansu; Rovere, Matteo; Shaw, Georgina M.; Reverberi, Daniele; Formica, Matteo; Quarto, Emanuele; Barry, Frank; Murphy, Mary; Gentili, Chiara (Frontiers in Bioengineering and Biotechnology, 2025)
Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) hold promise as a cell-free therapy for osteoarthritis (OA), due to their immunomodulatory and anti-inflammatory properties. However, the need for large-scale expansion to obtain MSC-EVs for clinical use can lead to senescence-related changes and loss of stem-like properties. In this scenario, induced pluripotent stem cell (iPSC)-derived MSCs (iMSCs) offer the unique opportunity to address obstacles associated with traditional MSC-based therapies. This study used a xeno-free (XFS) medium for long-term expansion of both MSCs and iMSCs, and their EVs comparison. Characterization of both cells and EVs was conducted across different passages, and the anti-inflammatory potential of EVs and iEVs was assessed using an in vitro model of osteoarthritis. Long-term expansion of MSCs resulted in cellular senescence and a reduction in trilineage differentiation capacity by passage five, accompanied by diminished anti-inflammatory properties of EVs. On the other hand, iMSCs exhibited batch-to-batch variability in differentiation and EV biological properties. However, the effects of iMSC-EVs were prolonged compared to MSC-EVs, providing a wider window of activity for therapeutic purposes. Despite this, the variability among iMSC batches poses challenges for their reliability in OA treatment. Further work is needed to overcome these limitations for clinical application.